2016
DOI: 10.1097/md.0000000000003845
|View full text |Cite|
|
Sign up to set email alerts
|

A meta-analysis and systematic review of randomized controlled trials with degarelix versus gonadotropin-releasing hormone agonists for advanced prostate cancer

Abstract: Our aim was to systematically evaluate the benefits of degarelix as antagonist versus agonists of gonadotropin-releasing hormones (GnRH) for the treatment of advanced prostate cancer (PC). This comparison was performed either in terms of biochemical or oncological or safety profiles. To this end we, carried out a systematic review and meta-analysis of the literature.We selected only studies directly and prospectively analyzing the two treatments in the same population (randomized phase III studies). We followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 17 publications
1
46
1
4
Order By: Relevance
“…One systematic review found no significant differences in risk for CV mortality between ADT and controls across all included studies (21). In other reviews, degarelix reduced the risk of CV events compared to GnRHa, as did IADT (12,15,25). There was a strong association between grade 3 cardiac adverse events and grade 3/4 vascular events and arbiraterone acetate + prednisone compared to placebo (23).…”
Section: Cardiac Disorders: Cardiovascular (Cv) Complications and Mormentioning
confidence: 99%
See 2 more Smart Citations
“…One systematic review found no significant differences in risk for CV mortality between ADT and controls across all included studies (21). In other reviews, degarelix reduced the risk of CV events compared to GnRHa, as did IADT (12,15,25). There was a strong association between grade 3 cardiac adverse events and grade 3/4 vascular events and arbiraterone acetate + prednisone compared to placebo (23).…”
Section: Cardiac Disorders: Cardiovascular (Cv) Complications and Mormentioning
confidence: 99%
“…Five systematic reviews referred to incidence of vasomotor flushing across various treatments and stages of PC from locally advanced to metastatic CRPC (14,15,25,29,57). Anti-androgens have a significantly lower risk of flashing than orchiectomy (RR 0.23; 95% CI 0.10, 0.27) (14) and GnRH agonists (<1% vs 45%) (57).…”
Section: C Hot Flashesmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In comparison, a metaanalysis of RCTs of phase III studies of degarelix, a GnRH antagonist, versus GnRH agonists found fewer reported severe adverse effects (1.6% v 3.6%, respectively), with an odds ratio of 0.55 (95% CI, 0.26 to 1.14) that favored the GnRH antagonist group. 30 Results of a clinical trial primarily evaluating cardiovascular outcomes between degarelix and leuprolide in men with advanced prostate cancer and preexisting cardiovascular disease are expected in 2020. 31 Treatment with the new hormonal agents, abiraterone and enzalutamide, has been associated with a 36% increased risk of cardiovascular events.…”
Section: Current Literature and Controversies In Adt And Cardiovasculmentioning
confidence: 99%
“…In the article “A meta-analysis and systematic review of randomized controlled trials with degarelix versus gonadotropin-releasing hormone agonists for advanced prostate cancer”, [1] which appeared in Volume 95, Issue 27 of Medicine , the fourth line of Table 2, “PSA progression-free survival in metastatic cases” was given incorrectly. The entry should have read “PSA progression rates in metastatic cases”.…”
mentioning
confidence: 99%